Performance of a Paired-End Sequencing-Based Noninvasive Prenatal Screening Test in the Detection of Genome-Wide Fetal Chromosomal Anomalies. (2nd June 2021) - Pertile, Mark D; Flowers, Nicola; Vavrek, Darcy; Andrews, Daniel; Kalista, Tasha; Craig, Andrew; Deciu, Cosmin; Duenwald, Sven; Meier, Kristen; Bhatt, Sucheta
Abstract: Background: Noninvasive prenatal tests (NIPTs) detect fetal chromosomal anomalies with high clinical sensitivity and specificity. We examined the performance of a paired-end sequencing-based NIPT in the detection of genome-wide fetal chromosomal anomalies including common trisomies, sex chromosomal aneuploidies (SCA), rare autosomal aneuploidies (RAAs), and partial deletions/duplications ≥7 Mb. Methods: Frozen plasma samples from pregnant women were tested using the VeriSeq NIPT Solution v2 assay. All samples were previously tested with a laboratory-developed NIPT and had known clinical outcomes. Individuals performing the sequencing were blinded to clinical outcome data. Clinical sensitivity and specificity were determined for basic (chromosomes 21, 18, 13, X, and Y) and genome-wide screening modes. Results: Of 2335 samples that underwent genome-wide analysis, 28 did not meet QC requirements, resulting in a first-pass assay failure rate of 1.2%. Basic screening analysis, excluding known mosaics, correctly classified 130/130 trisomy 21 samples (sensitivity >99.9%, 95% confidence interval [CI] 97.1%–100%), 41/41 trisomy 18 samples (sensitivity >99.9%, 95% CI 91.4%–100%), and 26/26 trisomy 13 samples (sensitivity >99.9%, 95% CI 87.1%–100%) with 6 false-positive results; specificities ≥99.90% were reported for all 3 trisomies. Concordance for SCAs ranged from 90.5%–100%. Genome-wide screening analysis including known mosaics correctly classified 27/28 RAAs and 20/27 partial deletions/duplications with a specificity of 99.80% for both anomalies, and an overall genome-wide specificity for all anomalies of 99.34%. Conclusions: The VeriSeq NIPT Solution v2 assay enables accurate identification of fetal aneuploidy, allowing detection of genome-wide fetal chromosomal anomalies with high clinical sensitivities and specificities and a low assay failure rate. Clinical Trial Notification [CTN] identification number [ID]: CT-2018-CTN-01585-1 v1, Protocol: NIPT T05 002.